2000
DOI: 10.1007/s005269900034
|View full text |Cite
|
Sign up to set email alerts
|

Multiple solutions of hemivariational inequalities with area-type term

Abstract: Hemivariational inequalities containing both an area-type and a non-locally Lipschitz term are considered. Multiplicity results are obtained by means of techniques of nonsmooth critical point theory. Mathematics Subject Classification (1991): 35J85 Recalls of nonsmooth analysisLet X be a metric space endowed with the metric d and let f : X → R be a function. We denote by B r (u) the open ball of centre u and radius r and we set

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…We apply a nonsmooth critical point theory developed in [10,12,13] and applied in [8,9,20] to treat the case of continuous functionals. r 2004 Elsevier Inc. All rights reserved.…”
mentioning
confidence: 99%
“…We apply a nonsmooth critical point theory developed in [10,12,13] and applied in [8,9,20] to treat the case of continuous functionals. r 2004 Elsevier Inc. All rights reserved.…”
mentioning
confidence: 99%
“…A first idea could be to apply the approach of Chang [8] to the locally Lipschitz functional f defined on BV ( ). However, it has been already observed that, in such a setting, the Palais-Smale condition fails even in the subcritical case, as the norm-convergence of BV cannot be usually obtained for a Palais-Smale sequence (see Marzocchi [29] and Degiovanni et al [15]). For this reason, it is more convenient to extend the functional f to L 1 * ( ) with value +∞ outside BV ( ).…”
Section: Introduction and Main Resultsmentioning
confidence: 97%
“…In this way the functional becomes only lower semicontinuous, but one can recover the Palais-Smale condition. We refer the reader to [12,14,21,24] for results in this direction.…”
Section: Introductionmentioning
confidence: 98%